Regulating child enticement in Malaysia: a comparative study with United States of America / Muhamad Izwan Ishak … [et al.] - Ishak, Muhamad Izwan; Ahmad Annual, NurHidayah; Ajmi, Mas Hana; Noordin, Mohd Fazreen Izuan (Faculty of Law, 2013)
For the last two semesters, we have been conducting a research on the law of enticement towards children in Malaysia with comparison to the criminal child enticement offences in the United States of America, in specific laws in states of California and Ohio. Instead of looking into the law, we also try to find the significance of the child enticement laws in the California and Ohio and try to adopt it with current situations happening in Malaysia as to whether its regulation suits to conditions in Malaysia. We also look on the weakness of the established laws in Malaysia with regards to child protection provisions in the Penal Code and the Child Act 2001 and try to propose a better provision of child enticement offences by including improvisation of the current provisions available in the new proposed provision in the Penal Code.